2000
DOI: 10.1017/s0007114500000441
|View full text |Cite
|
Sign up to set email alerts
|

Validation of dietary intakes measured by diet history against24 h urinary nitrogen excretion and energy expenditure measuredby the doubly-labelled water method in middle-aged women

Abstract: A diet history method for estimating energy and N intakes was validated against 24 h urinary N excretion and energy expenditure measured by the doubly-labelled water (DLW) method. Fortyeight women aged 50-65 years were studied over 1 year. Weighed diet records from 4 d and two 24 h urine collections, for measurement of urinary N excretion, were obtained in each of four seasons. At the end of the year, a diet history was obtained, BMR was measured by whole-body calorimetry, and, in sixteen women, total energy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 36 publications
9
46
0
Order By: Relevance
“…In contrast with most (Jain et al, 1980;Hankin et al, 1991;Block et al, 1992;Jain et al, 1996;Black et al, 2000), but similar to other previous studies (Huenemann & Turner, 1942;Mahalko et al, 1985) we observed that the 7 day food record gave slightly higher nutrient estimates than the diet history interview. As compared to the more widely used structured interviews with specific questions on a large number of frequently consumed food, the traditional interview technique with non-leading and open-ended questions used in our study may tend to underestimate daily intake.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast with most (Jain et al, 1980;Hankin et al, 1991;Block et al, 1992;Jain et al, 1996;Black et al, 2000), but similar to other previous studies (Huenemann & Turner, 1942;Mahalko et al, 1985) we observed that the 7 day food record gave slightly higher nutrient estimates than the diet history interview. As compared to the more widely used structured interviews with specific questions on a large number of frequently consumed food, the traditional interview technique with non-leading and open-ended questions used in our study may tend to underestimate daily intake.…”
Section: Discussionsupporting
confidence: 90%
“…As compared to the more widely used structured interviews with specific questions on a large number of frequently consumed food, the traditional interview technique with non-leading and open-ended questions used in our study may tend to underestimate daily intake. However, as observed by others (Black et al, 2000), we found a close quantitatively agreement between the two methods and a small individual variation of the lack of agreement suggesting that for practical purposes the difference between methods in assessing energy and macronutrient intake is negligible. Figure 2 The between-method difference (diet history interview and 7 day food records) in assessment of total daily energy intake plotted against the average energy intake estimated from both methods with indication of the median difference and limits of agreement (BlandAltman plot).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the positive N balance of growing children and adolescents represents a specific methodological challenge. Therefore, our study took advantage of an ongoing longitudinal study, while validation studies in adults were mostly experimental and especially designed to assess validity (21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…The method has previously been validated against 24-h urinary nitrogen excretion (Black et al, 2000) and is believed to place fewer burdens and obtain a better measure of long-term habitual intakes than diet records (Hankin, 1986). All diet histories were collected between the months of October and April to minimize effects of seasonal variations of dietary habits.…”
Section: Dietary Assessmentmentioning
confidence: 99%